Farmer’s Logbook - Thi Le, Tam; Giang Thi Thu Luu; Simelton, Elisabeth; Chi Thi Linh Le; Duong, Minh Tuan; Hoa Dinh Le; Huong Thi Tong (2018)
This logbook is designed for farmers to observe weather, management, outputs, and impacts of a farming practice. This logbook aims to: encourage farmers to document their observations and management; to monitor and evaluate interventions; and to encourage social learning.